2000
DOI: 10.1128/jvi.74.19.8785-8792.2000
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus Type 1 Nucleocapsid Protein Can Prevent Self-Priming of Minus-Strand Strong Stop DNA by Promoting the Annealing of Short Oligonucleotides to Hairpin Sequences

Abstract: Understanding how viral components collaborate to convert the human immunodeficiency virus type 1 genome from single-stranded RNA into double-stranded DNA is critical to the understanding of viral replication. Not only must the correct reactions be carried out, but unwanted side reactions must be avoided. After minus-strand strong stop DNA (؊sssDNA) synthesis, degradation of the RNA template by the RNase H domain of reverse transcriptase (RT) produces single-stranded DNA that has the potential to self-prime at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(87 citation statements)
references
References 42 publications
6
81
0
Order By: Relevance
“…Interestingly, the 2Ј-O-methyl modification greatly reduced the self-priming product in both the donor extension and strand transfer reactions (data not shown). This is not surprising, since the uncleaved 16-nt RNA fragment would remain annealed to the 3Ј-end of cDNA and thereby inhibit it from folding back and self-priming, as shown previously by the Hughes group (50,58,77).…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…Interestingly, the 2Ј-O-methyl modification greatly reduced the self-priming product in both the donor extension and strand transfer reactions (data not shown). This is not surprising, since the uncleaved 16-nt RNA fragment would remain annealed to the 3Ј-end of cDNA and thereby inhibit it from folding back and self-priming, as shown previously by the Hughes group (50,58,77).…”
Section: Resultsmentioning
confidence: 90%
“…A ladder of pause sites was observed from position 47 through 53. Analysis of the predicted secondary structure of this region suggested that the pausing ladder was due to displacement synthesis through an alternate hairpin structure formed from refolding of the template, as shown previously (50).…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Studies have shown that all these three steps need the participation of NC proteins, especially the minus stand transfer step. 66,[78][79][80] The effect of NC's chaperone activity on these processes is detailed in the review by Levin and Musier-Forsyth in this special issue.…”
Section: Na Chaperone Proteins: Retroviral Nc Proteinsmentioning
confidence: 99%